Kecepatan Potong, Kecepatan Pemakanan dan Sudut Potong Utama Terhadap Kekasaran Permukaan pada Proses Bubut Medium Carbon Steel - Gultom, Peniel Immanuel; Kiswandono (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Competition in the manufacturing industry demands products with high quality and high productivity too. Machining parameters such as cutting angle, cutting speed, and feed speed determine the rate of material works or the rate of material removal (MRR) of the lathe process. Determination of excessive machining parameters will reduce productivity because there is a product that must be reworked. This research will specifically emphasize the lathe process with medium carbon steel workpieces. The problem is how to specify its cutting speed, feed speed, and the primary cutting angle in the lathe process with a medium carbon steel workpiece that will produce a smooth surface of the lathe on the product. The workpiece used in the experiment is ST 60 steel dimensions Ø30 mm x 200 mm with a chuck-tailstock spindle gripping system. The results showed that the ST-60 steel lathe process without followers, with the primary cutting angle machining parameters Kr = 45°, cutting speed 60.5 m /min, feeding speed 44.66 mm/min, and at a depth of cut 0.2 mm obtained surface roughness value 3.72 μm or N8 roughness level. As for the primary cutting angle machining parameters Kr = 90°, cutting speed 60.5 m/min, feeding speed 22.33 mm/min, and at a depth of cut 0.2 mm, the surface roughness value 3.69 μm or N8 roughness level is obtained.